Influence of exposing dental implants into the sinus cavity on survival and complications rate: a systematic review - Gian Maria Ragucci; Basel Elnayef; Fernando Suárez-López del Amo; Hom-Lay Wang; Federico Hernández-Alfaro; Jordi Gargallo-Albiol (SpringerOpen, 2019)
Abstract Background After tooth loss, the posterior maxilla is usually characterized by limited bone height secondary to pneumatization of the maxillary sinus and/or collapse of the alveolar ridge that preclude in many instances the installation of dental implants. In order to compensate for the lack of bone height, several treatment options have been proposed. These treatment alternatives aimed at the installation of dental implants with or without the utilization of bone grafting materials avoiding the perforation of the Schneiderian membrane. Nevertheless, membrane perforations represent the most common complication among these procedures. Consequently, the present review aimed at the elucidation of the relevance of this phenomenon on implant survival and complications. Material and methods Electronic and manual literature searches were performed by two independent reviewers in several databases, including MEDLINE, EMBASE, and Cochrane Oral Health Group Trials Register, for articles up to January 2018 reporting outcome of implant placement perforating the sinus floor without regenerative procedure (lateral sinus lift or transalveolar technique) and graft material. The intrusion of the implants can occur during drilling or implant placement, with and without punch out Schneiderian. Only studies with at least 6 months of follow-up were included in the qualitative assessment. Results Eight studies provided information on the survival rate, with a global sample of 493 implants, being the weighted mean survival rate 95.6% (IC 95%), after 52.7 months of follow-up. The level of implant penetration (≤ 4 mm or > 4 mm) did not report statistically significant differences in survival rate (p = 0.403). Seven studies provided information on the rate of clinical complications, being the mean complication rate 3.4% (IC 95%). The most frequent clinical complication was epistaxis, without finding significant differences according to the level of penetration. Five studies provide information on the radiographic complication; the most common complication was thickening of the Schneiderian membrane. The weighted complication rate was 14.8% (IC 95%), and penetration level affects the rate of radiological complications, being these of 5.29% in implant penetrating ≤4 mm and 29.3% in implant penetrating > 4 mm, without reaching statistical significant difference (p = 0.301). Conclusion The overall survival rate of the implants into the sinus cavity was 95.6%, without statistical differences according to the level of penetration. The clinical and radiological complications were 3.4% and 14.8% respectively. The most frequent clinical complication was the epistaxis, and the radiological complication was thickening of the Schneiderian membrane, without reaching statistical significant difference according to the level of implant penetration inside the sinus.